Non-precious-metal catalysts for alkaline water electrolysis: operando characterizations, theoretical calculations, and recent advances. (3rd November 2020) - Wang, Jian; Gao, Yang; Kong, Hui; Kim, Juwon; Choi, Subin; Ciucci, Francesco; Hao, Yong; Yang, Shihe; Shao, Zongping; Lim, Jongwoo
Abstract : Advances of non-precious-metal catalysts for alkaline water electrolysis are reviewed, highlighting operando techniques and theoretical calculations in their development. Abstract : Recent years have witnessed an upsurge in the development of non-precious catalysts (NPCs) for alkaline water electrolysis (AWE), especially with the strides made in experimental and computational techniques. In this contribution, the most recent advances in NPCs for AWE were systematically reviewed, emphasizing the application of in situ / operando experimental methods and density functional theory (DFT) calculations in their understanding and development. First, we briefly introduced the fundamentals of the anode and cathode reaction for AWE, i.e., the oxygen evolution reaction (OER) and the hydrogen evolution reaction (HER), respectively. Next, the most popular in situ / operando approaches for characterizing AWE catalysts, including hard and soft XAS, ambient-pressure XPS, liquid and identical location TEM, electrochemical mass spectrometry, and Raman spectroscopy were thoroughly summarized. Subsequently, we carefully discussed the principles, computational methods, applications, and combinations of DFT with machine learning for modeling NPCs and predicting the alkaline OER and HER. With the improved understanding of the structure–property–performance relationship of NPCs for AWE, we proceeded to overview their current development, summarising state-of-the-art design strategies to boost their activity. In addition, advances in various extensively investigated NPCs for AWE were evaluated. By conveying these methods, progress, insights, and perspectives, this review will contribute to a better understanding and rational development of non-precious AWE electrocatalysts for hydrogen production.